Guide to the Geologic Map of Illinois - Illinois State Geological Survey (Salt Lake City, UT : Project Gutenberg, 2021)
"Guide to the Geologic Map of Illinois" by Illinois State Geological Survey is a scientific publication produced in the early 1960s. This educational guide focuses on the geology of Illinois, particularly highlighting the state's geologic features and formations resulting from past glacial activities, offering insights into the complex history of the earth's geology in this region. The content of the book elaborates on various geological processes, specifically detailing the effects of glaciation on Illinois's landscape around 15,000 years ago. It discusses the types of rocks found beneath the glacial drift, the layers of bedrock, structural geology, and economic geology, including the state's mineral resources such as coal, petroleum, limestone, and dolomite. The guide provides a detailed mapping of these resources, accompanied by explanations of the geological history and the methods used in geological exploration. Overall, it serves as a foundational resource for understanding the geological makeup of Illinois and its historical significance. (This is an automatically generated summary.)
Release date is 2021-06-26
Stephen Hutcheson and the Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: Geology -- Illinois; Geology -- Illinois -- Maps